Penerapan Problem-Based Learning pada Mata Pelajaran Instalasi Penerangan Listrik - Azzikri, Muhammad Fadhel; Yuhendri, Muldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2024)
This study aims to determine the effectiveness of problem-based learning methods in electrical lighting installation subjects at SMK Negeri 1 West Sumatra. Student learning outcomes are still low due to the methods used that are not suitable, this results in students being less active in the learning process. Therefore, it is necessary to conduct research using problem-based learning methods to see the effectiveness of student learning outcomes. The research design used is Pre-Experimental Design using the One Group Pretest-Posttest design. In this study, the instruments used include initial test questions (pretest), and final test (posttest). Pretest and posttest were used in this study to collect data. Data analysis techniques used in this study are student learning completeness, effect size analysis, and mann whitney test. Based on the research findings, it is proven that the students of class XI TITL 1 SMKN 1 West Sumatra using problem-based learning method in the subject of electrical lighting installation is very effective. Based on the results of data analysis and discussion, it can be concluded that the use of problem-based learning methods is effective in improving the learning outcomes of students in class XI TITL 1 in the subject of Electrical Lighting Installation. This can be seen from the increase in student learning after treatment. Evidenced by the level of completeness of student learning outcomes that increased and the average posttest score of 87% which was higher than the average pretest score of 73,4. In addition, the results of the effect size analysis show that the use of problem-based learning methods has a large impact on student learning outcomes of 0,78. There is a significant difference between the learning outcomes of the experimental and control classes, so the use of problem-based learning methods is said to be effective.